Evaluation of the gap area between two sided friction stir welding of AA 2024-T351 - Mahdi, Hassan; Tolephih, Moneer; Namer, Nasri (International Journal of Engineering and Technology, 2018)
The joints fabricated by two sided friction stir welding has shown higher ultimate tensile strength as compared to the joints fabricated by single pass and this trend is common for all the tool profiles. The joining of AA 2024-T351 aluminum plates with dimensions 200 mm ´ 200 mm ´ 5 mm (Length ´ width ´ thickness) was carried out by double pass friction stir welding (FSW) technique. Three friction stir welding tools with different pin height (1, 1.5 and 2) mm were used with different stirring rotation speeds and travel speed, (560, 710 and 900) RPM and (16, 20 and 25) mm/min respectively. The welded specimens were analyzed and evaluated using microstructure, macrostructure, tensile and hardness tests. The results indicated that the yield strength and tensile strength increases as the distance between the two passes (double pass) decrease, the rotational speed of 900 RPM and 560 RPM with travel speed of 16 mm/min and 25 mm/min, respectively is considered to be the most efficient and the width of the gap of the joint line decrease as the distance between the two welding pass decreases.